The Usefulness of a News Media Literacy Measure in Evaluating a News Literacy Curriculum. (June 2017) - Maksl, Adam; Craft, Stephanie; Ashley, Seth; Miller, Dean
A survey of college students showed those who had taken a news literacy course had significantly higher levels of news media literacy, greater knowledge of current events, and higher motivation to consume news, compared with students who had not taken the course. The effect of taking the course did not diminish over time. Results validate the News Media Literacy Scale and suggest the course is effective in helping equip students to understand and interpret news.